Verskillende scenario"s met die oog op privaat-kerkskool, staatsondersteunde en staatskool in "n veranderende onderwysbedeling - Steenkamp, L. J. S. (Hervormde teologiese studies, 1994)
Models of education in the new South Africa: Private church schools or state-aided community schools? The Nederduitsch Hervormde Church sees the basis of teaching and education to be a mother-tongue Christian education, culturally directed and of a high standard. Apart from the role of the Church, the state also has a responsibility towards the education of the child. This responsibility cannot be evaded. In the heterogeneous composition of the South African population, community schools are the obvious solution. The state-supported community school is cheaper than private or church schools, and at the same time it gives the state the attractive option of having the parents make a greater financial contribution to these schools. The statesupported community school, moreover, provides a worid-wide recognized model, founded on healthy and accredited educational principles. Nevertheless, very necessary and unavoidable adaption to this model has seriously to be considered by the church, by means of the continued and supplementary education of teachers in their thoughts and their outlook on life.